Analisis Sejarah Interaksi Peradaban Cina dengan Islam - Azka, Nur Rohmatul; Firdaus, Endis; Kosasih, Aceng (Tarikh : Journal of Islamic History and Civilization, 2025)
This research aims to describe the interaction of Chinese civilization with islām. The method used is descriptive analysis. Based on the results of the analysis, the interaction between the Chinese people and the Arabs occurred during the 5th century AD, which is long before the religion of Islām was born. One of the famous Muslim leaders in the process of spreading Islām in China is Sa'ād Ibn Abī Waqās through the “Silk Road”. Islām has been rooted in China for a long time, starting from the Tang Dynasty to the Manchu Dynasty. The golden age of Muslims was during the Ming Dynasty. Unfortunately, when China was transformed into the People's Republic of China (PRC), with an anti-islām communist system, the islām community in the country was like chicks who lost their mother, because all the teachings of islām began to cease to function at that time. However, the spirit of the Muslim minority in the region has never faded. Islām, which was introduced by devout and intelligent merchants centuries ago, has been deeply rooted and influential in many aspects of Muslim life in China, not only in thought, but also in the value system and norms of the Muslim community in China today. Whether we realize it or not, the Chinese people have adopted a lot of islām knowledge from time to time.